Reconstructing Zakatable Assets in Insurance and Takaful under MUIS Singapore Guidelines through the Doctrine of Al-Milk al-Tām - Agie Hilal Azizi; Fuad Thohari; Euis Amalia; Nurhasanah Nurhasanah; Nisrina Mutiara Dewi (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2026)
The determination of zakatable assets in insurance and takaful remains a contemporary issue in Islamic jurisprudence, particularly regarding the requirement of complete ownership (al-milk al-tām). This study examines the construction of zakatable assets under the Singapore Islamic Religious Council (MUIS) guideline and evaluates their conformity with the doctrine of al-milk al-tām. Employing a normative juridical method with conceptual and uṣūl al-fiqh approaches, the study analyses the MUIS guideline, zakat calculator, and institutional clarification to examine the legal basis for determining zakatable assets in insurance and takaful. The analysis demonstrates that MUIS consistently identifies surrender value as the zakatable asset in conventional insurance. In the case of takaful, the available normative and institutional materials allow the reconstruction of four possible legal constructions concerning annual premium, cumulative premium, and cash value as potential zakatable assets. The findings indicate that premium-based constructions encounter difficulties under the doctrine of al-milk al-tām because contributions allocated to the collective tabarru’ fund are no longer subject to the participant’s exclusive ownership and control. By contrast, cash value provides the closest approximation to al-milk al-tām because it represents an identifiable and claimable financial entitlement. Nevertheless, its definitive juristic status remains dependent on whether the claimable amount exclusively reflects the participant’s proprietary investment interest or also incorporates elements attributable to the collective tabarru’ fund. The study contributes to contemporary Islamic legal scholarship by demonstrating that the doctrine of al-milk al-tām offers a coherent analytical framework for distinguishing contractual contributions from claimable financial entitlements in determining zakatable assets within contemporary insurance and takaful arrangements.